Evaluation of antidiabetic effect of Cissampelos pareira L. (Menispermaceae) root extract in streptozotocin-nicotinamide-induced diabetic rats via targeting SGLT2 inhibition - Ankit Kumar; Ravindra Semwal; Ashutosh Chauhan; Ruchi Badoni Semwal; Subhash Chandra; Debabrata Sircar; Partha Roy; Deepak Kumar Semwal (Elsevier, 2022)
Background: Cissampelos pareira L. (Menispermaceae) has been used in Indian traditional medicine for a variety of human ailments including diabetes mellitus. Although its anti-hyperglycemic activity has been validated by previous studies, a detailed mechanism of action and the responsible components are still unknown. Purpose: The present study aimed to evaluate the antidiabetic effect of aqueous-ethanolic extract of C. pareira roots in streptozotocin-nicotinamide (STZ-NAM)-induced diabetic rats via targeting SGLT2 inhibition. Methods: In vitro α-amylase and α-glucosidase inhibitory assays were conducted using Epoch Microplate Spectrophotometer. A-498 cells viability assay and SGLT2 protein expression study were conducted using MTT assay and western blot respectively. STZ-NAM-induced diabetic rats were used as a model to evaluate the antidiabetic effect of the extract. Selected bioactive compounds reported earlier from the plant were studied for their in silico SGLT2 inhibitory activity. Results: The extract showed α-amylase and α-glucosidase inhibitory effects with IC50 values of 18.0 ± 1.01 and 4.87±0.54 mg/mL, respectively. A-498 cells viability assay showed its CC50 value of 0.8 mg/mL. The extract showed a notable effect on SGLT2 protein expression. The in vivo study revealed that the extract significantly (p<0.05) reduced the glucose levels in rats at the dose of 500 mg/kg, b.w. in a 28-days study. The molecular docking studies revealed insulanoline and warifteine as the most active compounds with docking scores of -10 and -9.9 kcal mol−1, respectively. Conclusion: The study showed that the extract has the potential to reduce STZ-induced elevated blood glucose without affecting liver and kidney functions.